Critical Appraisal on Central Place Theory of Christaller in the Context of Nepal - Kuikel, Shachita (Rural Development Journal, 2025)
This paper critically analyzes the central place theory of Walter Christaller to connect the relationship of rural urban linkage in Nepal. The study draws on diverse perspectives and differing geographical structure of Nepal with Southern Germany in regard of rural urban linkage. It is a theory of geographical perspective developed in the early 20th century by Christaller which can have nexus of the context of Nepal in some extent. This paper attempts to explain how cities and other settlements are spatially distributed and how they interact with each other in isotropic spaces and can be compared in heterogeneous geography like Nepal. The finding reveals the nexus of this theory in the context of Nepal with the spatial behavior of People.